Dynamic properties of low-density expandable polystyrene concrete materials - Jue Han; Hualin Fan (Defence Technology)
Expanded polystyrene (EPS) concrete, known for its environmental friendliness, energy absorption capacity, and low impedance, has significant potential application in the fields of wave absorption and vibration reduction. This study designed and prepared EPS concrete materials with four levels of density. Quasi-static uniaxial compression and Split Hopkinson Pressure Bar (SHPB) impact tests were conducted to obtain stress-strain curves, elastic moduli, failure modes, energy absorptions, and strain rate effects of the EPS concrete under quasi-static and dynamic loading conditions. The influences of density on various performance indicators were analyzed. By combining the Zhu-Wang-Tang (ZWT) constitutive model with a modified elastic-brittle model, a modified dynamic constitutive model was proposed. The accuracy of the model was validated by the experimental data. The results indicate that the addition of EPS particles enhances the ductility of the EPS concrete. The EPS concrete has significant strain rate effect, which gets stronger as density increases. The modifiedconstitutive model accurately characterizes the dynamic stress-strain curves of the EPS concrete.